Badminton agility training device - Mohd Hasnun Ariff, Hassan; Muhammad Aizzat, Zakaria; Muhammad Amirul, Abdullah; Anwar, P. P. Abdul Majeed (2018)
Badminton is one of the most popular sports in Malaysia. This sport requires the athlete to be agile, running around the court to return the shuttlecock. One of the most important training in badminton is the footwork training. This training is conducted on the court without using any shuttlecock. In this drill, the coach stands in front of the players and shows the location where the player needs to go. The players will go to the instructed location, perform an action of a badminton shot, and return to the centre point. This drill is done for a few minutes. This project aims to replace the need of the coach to stand in front by creating an intelligent electronic training device.